2019
DOI: 10.1186/s13765-019-0429-1
|View full text |Cite
|
Sign up to set email alerts
|

Bioremoval of reactive dye Remazol Navy by kefir grains

Abstract: Potential use of living and non-living kefir grains (small, gelatinous white/yellow irregularly shaped masses consist of live bacteria and yeasts) on removal of reactive dye Remazol Navy RGB from aqueous solutions were investigated. Experiments were carried out under different process conditions in order to optimize and model the bioremoval processes. At all conditions the living kefir grains exhibited higher dye removal efficiencies than the non-living grains. In 180 min, 96.3% and 79.4% dye removal was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
0
4
0
1
Order By: Relevance
“…9) [30]. The linearized pseudo-first-order, (5) pseudo-second-order, and intra-particle diffusion kinetic models are defined by Eqs. 7, (8) and (9), respectively [30,31]:…”
Section: Biosorption Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…9) [30]. The linearized pseudo-first-order, (5) pseudo-second-order, and intra-particle diffusion kinetic models are defined by Eqs. 7, (8) and (9), respectively [30,31]:…”
Section: Biosorption Kineticsmentioning
confidence: 99%
“…Soluble heavy metal components are not biodegradable and they tend to accumulate in living organisms as well as oceans, lakes, and rivers [4]. Common methods used to separate heavy metals from industrial wastewaters include chemical precipitation, filtration, reverse osmosis, membranes, ion exchange and adsorption [5]. There are a variety of treatment processes deployed to remove heavy metal ions from the environment, but these, typically, are associated with expensive running costs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported the uses of kefir in terms of food applications, cosmetic purposes, and industries due to the physicochemical, microbiological, and bioactive compound contained in kefir [19,20,21]. Kefir has been used as an ingredient in wine production, kefir cereal-based beverages, kefir facial mask, and dyes [22]. Further studies into the characterization of specific microbial compositions in kefir grains, mainly the Lactobacillus species, is of utmost interest, especially from Malaysia where the production conditions vary between regions.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of mutagenic effect of azo dye metabolite samples from aerobic cultures with probiotic could be clarified by the presence of an adequate level of dissolved oxygen that might limit the azo-reductase action and raise the oxygenase activity; thus granting the decolorization of the dye aromatic amines to which the mutagenic effects may be assigned. Marques et al [45], Nakayama et al [46], Sweeney et al [47], Erdoğdular and Dilek [48] and Jayalakshmi and Jeyanthi [49] reported that carcinogenicity via mutagenicity of some azo dyes and allied aromatic amines could be engendered Fig. 7.…”
Section: Mutagenicity Assessmentmentioning
confidence: 99%